人乳脂肪酸组分与新生儿母乳性黄疸的相关性分析 (Zhongguo Dang Dai Er Ke Za Zhi, 2020)
OBJECTIVE: To study the association of fatty acid composition in human milk with breast milk jaundice (BMJ) in neonates. METHODS: A total of 30 full-term neonates who were admitted to the neonatal intensive care unit from October 2016 to October 2017 and were diagnosed with late-onset BMJ were enrolled as the BMJ group. Thirty healthy neonates without jaundice or pathological jaundice who were admitted to the confinement center during the same period of time were enrolled as the control group. Related clinical data were collected, including sex, mode of birth, feeding pattern, gestational age, birth weight, gravida, parity, and peak level of total serum bilirubin. Breast milk was collected from the mothers, and the MIRIS human milk analyzer was used to measure macronutrients (fat, protein, and carbohydrate) and calorie. Gas chromatography was used to analyze the content of different fatty acids in breast milk. RESULTS: The control group had higher levels of macronutrients in human milk than the BMJ group, with significant differences in fat, dry matter, and calorie (P < 0.05). In addition, 25 fatty acids were detected in breast milk, including 9 saturated fatty acids, 6 monounsaturated fatty acids, and 10 polyunsaturated fatty acids. The comparison of the percentage composition of different fatty acids showed that compared with the control group, the BMJ group had significantly lower percentage compositions of C15:0, C16:0, C17:0, C18:0, C20:0, C18:1n9t, C20:1n9, C18:3n6, C22:2, and C22:6n3 (DHA) and higher percentage compositions of C10:0, C12:0, C14:0 in breast milk (P < 0.05). CONCLUSIONS: Some macronutrients and fatty acid composition in human milk may be associated with the pathogenesis of BMJ in neonates.